Optimisation de la réponse des dosimètres Radiophotoluminescence : facteur d’ouverture de la collimation et réponse énergétique - GHEMAM AMARA, Soumaya (My University, 2016)
دفنا هو دراسة استجابة اثنين من مقاييس الجرعات (الكواشف) الزجاجية RPL GD-302و RPL GD-450من حيث تاثيرالسطح (الحقل) الإشعاعي والاستجابة الطاقوية. في هذه الدراسة استخدمنا برنامج محاكاة يعتمد على طريقة ''مونتي كارلو'' وهو ، MCNP5لحساب معامل السطح الإشعاعي مع حقل من 5 × 5إلى 20 × 20سم ،2والاستجابة الطاقوية لحزم إشعاعية متوسطة الطاقة متوسطة من 50إلى 200كيلو فولت و حزم إشعاعية عالية الطاقة من 6إلى 25ميغافولت مع إستعمال حزمة أشعة غاما 60Coكحزمة إشعاع مرجعية. نتائجنا تظهر ان عامل تاثيرالسطح (الحقل) الإشعاعي والاستجابة الطاقوية مع الحزم العالية الطاقة جيدة و قابلة للمقارنة مع الأبحاث المنشورة، على العكس مع الحزم المتوسطة الطاقة فالإستجابة الطاقوية عالية جدا وبالتالي غير مقبول. وفي الختام، مقاييس الجرعات (الكواشف) الزجاجية RPL GD-302و RPL GD-450دون المرشحات يمكن أن تستخدم كمفاييس (كواشف) للمعايرة في العلاج الإشعاعي، كما لا ينصح بإستخدامها كمقاييس للجرعات الشخصية في مجالات تشخيص الشعاعيOur objective is to optimize the response of two glass dosimeters RPL GD-302 and GD-450 without filters in terms of output factor and energy response . In this study we used the Monte Carlo code MCNP5, to calculate the output factor with a field size of 5 × 5 field 20 × 20 cm2, and the energy response of medium energy beams for 50 to 200 kV and high energy beams for 6 to 25 MV with 60Co beam as reference beam. Our results show that output factor and the energy response with mega-voltage beams (high energy) are very comparable with published papers, against energy response with kilo-voltage beams (medium energy) is very high and therefore not acceptable. In conclusion, the two glass dosimeter RPL GD-302 and GD-450 without filters can be used as calibration dosimeter in radiation therapy, by cons are not recommended to use as personal dosimeters in the areas of radiodiagnostic
memoire master physique
Keywords: : مقاييس الجرعات ، RPLمحاكاة مونت كارلو ،MCNPتاثيرالسطح (الحقل) الإشعاعي, الاستجابة الطاقوية; Radiophotoluminescence dosimeters RPL, Monte Carlo simulation, opening, output factor, energy response